Pengaruh Kualitas Layanan dan CRM terhadap Loyalitas Pelanggan dengan Kepuasan sebagai Variabel Mediasi : Studi Wewe Travel - Maria Magdalena; Wahju Wulandari; Mulyono Mulyono (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
In this area service is very important with many people who use it to travel far or near or just send package. Data analysis using path analysis with the help of SPSS 27 and SmartPLS 4.0 software. The results of the study indicate 1) there is no significant effect of service quality on customer satisfaction 2) there is a significant effect of customer relationship management on customer satisfaction 3) there is a significant effect of customer satisfaction on customer loyalty 4) there is an effect of service quality on customer loyalty 5) there is an insignificant effect of customer relationship management on customer loyalty 6) there is an insignificant effect of service quality on customer loyalty through customer satisfaction 7) there is a significant effect of customer relationship management on customer loyalty through customer loyalty.